Tumor-Derived Exosomes Modulate Primary Site Tumor Metastasis - Bai, Suwen; Wang, Zunyun; Wang, Minghua; Li, Junai; Wei, Yuan; Xu, Ruihuan; Du, Juan (Frontiers in Cell and Developmental Biology, 2022)
Tumor-derived exosomes (TDEs) are actively produced and released by tumor cells and carry messages from tumor cells to healthy cells or abnormal cells, and they participate in tumor metastasis. In this review, we explore the underlying mechanism of action of TDEs in tumor metastasis. TDEs transport tumor-derived proteins and non-coding RNA to tumor cells and promote migration. Transport to normal cells, such as vascular endothelial cells and immune cells, promotes angiogenesis, inhibits immune cell activation, and improves chances of tumor implantation. Thus, TDEs contribute to tumor metastasis. We summarize the function of TDEs and their components in tumor metastasis and illuminate shortcomings for advancing research on TDEs in tumor metastasis.